A review of organizational and individual career management: A dual perspective - Wesarat, Phathara-on; Sharif, Mohmad Yazam; Abdul Majid, Abdul Halim (Macrothink Institute, 2014)
This paper views career management as a combination of both organizational career management (OCM) and individual career management (ICM).It highlights the important impact of career management on personal and organizational successes.It also emphasizes on the effective career management which fosters personal career growth and sustains organizational competitive advantages.At the personal level, the notion of career management brings forth the employee’s capability to develop a career in the workplace. Likewise, it provides organizations with the ability to proactively respond to the rapidly changing organizational environments.This paper differentiates between OCM and ICM that could lead to a clearer understanding of the two terms.The concept of career management is important to academics and practitioners who are involved in this area.